Adsortive removal of copper from aqueous solution by agro-industrial waste adsorbent - Che Zulzikrami, Azner Abidin; Fahmi, Muhamad Ridwan; Naimah, Ibrahim; Masitah, Hassan; Salsuwanda, Selamat; Nazerry Rosmady, Rahmat (Universiti Kebangsaan Malaysia (UKM), 2011)
Regional Engineering Postgraduate Conference 2009 (EPC 2009) organized by Faculty of Engineering & Built Environment, Universiti Kebangsaan Malaysia, from 20th - 21st October 2009 at Palm Garden Hotel, Putrajaya, Malaysia.